An Application of the Dagum Type III Model to Measure Household Net Wealth Inequality in Indonesia - Soseco, T.; Olivia, S.; Oxley, Leslie (2024)
This paper applies the Dagum Type III model to measure household net wealth inequality in Indonesia utilising data from the Indonesian Family Life Survey (IFLS) 1993–2014. The results are the distribution of household net wealth in Indonesia is right-skewed, with long-and sparse-hand tails that reflect a large proportion of households that have very low net wealth and a small proportion of households that have very high net wealth. Further, the inequality of household net wealth in Indonesia declined, as shown by the decrease in the Gini coefficient.